2018
DOI: 10.1016/j.burns.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation practices for burn survivors in low and middle income countries: A literature review

Abstract: The published research on burns rehabilitation is very limited and little is known about current practices in LMIC settings. In order to inform policy and service delivery, the effectiveness, feasibility and sustainability of current services needs to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The model of early rehabilitation for people with burns is still relatively novel, and we are aware of only a handful of healthcare settings in Egypt that have begun burn rehabilitation programs. According to Jagnoor et al (2018), it is unknown what burn rehabilitation services are accessible, available, or most useful for rehabilitation centers in developing nations, as (Lotfi et al, 2020;Procter, 2010). In addition, this model of care was developed in response to a global demand for early and continuous rehabilitation care for patients with burns (Herzog et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The model of early rehabilitation for people with burns is still relatively novel, and we are aware of only a handful of healthcare settings in Egypt that have begun burn rehabilitation programs. According to Jagnoor et al (2018), it is unknown what burn rehabilitation services are accessible, available, or most useful for rehabilitation centers in developing nations, as (Lotfi et al, 2020;Procter, 2010). In addition, this model of care was developed in response to a global demand for early and continuous rehabilitation care for patients with burns (Herzog et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study findings highlight the inadequacy of the current burn rehabilitation support programmes across both settings with an increased likelihood of missing out on transitional care needs. A review that explored the rehabilitation practices for burn survivors in LMICs observed that although psychiatric disorders are prevalent among burn survivors, the focus of most rehabilitation programmes is improving physical health with limited to attention to other domains of the burn survivor (Jagnoor et al, 2018b). The needs of burn survivors, though distinct, may be inter-related which is indicative that even if only physical health improves, challenges in other domains may mask the observed improvement (Bayuo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The rehabilitation of an acid burn patient is difficult, time-consuming and yet undeniably an integral part of their management. 11,12 As noted, the long-term effects of burns are wide-ranging including the fear of social engagement and depression, and the ever-present risk of suicide. 13 Reliable data on the number of acid attack survivors who commit suicide are unfortunately lacking due to under-reporting and the lack of central registries.…”
Section: Rehabilitationmentioning
confidence: 99%